Synergistic adsorption of MICB/1-Heptanol and MIBC/1-Octanol mixtures at air/water interface - Le, Thu; Phan, Chi; Ang, Ha Ming (Engineers Australia, 2011, 2011)
Though aliphatic frothers used in industry are mostly in mixed form, fundamental understanding of mixed adsorption, especially the synergistic effects, remains unsatisfactory. In this study, the adsorption of MIBC, a popular frother with the branching structure, with 1-heptanol and 1-octanol is investigated at air/water interface. The adsorption behaviour of MIBC/1-heptanol is similar with other mixtures of straight chain alcohols (1-heptanol/1-octanol, 1octanol/1-hexanol) reported in literature. However, the mixture of MIBC/1-octanol demonstrated a synergistic effect, which can be contributed by branching structure of MIBC. The experimental results were analysed mathematically using Fairnerman’s binary adsorption model. The influence of branching structure on molecular arrangements in adsorption layer and flotation process is also discussed.